2023
DOI: 10.3389/fenvs.2023.1099942
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and influencing factors of soil SOC、DOC、ROC at initial stage of vegetation restoration in a karst area

Abstract: Vegetation restoration has always been the focus of ecological research, but the synergistic effect of the soil carbon cycle and vegetation restoration succession process in karst area is still unclear. In this study, the complete succession zones of non-karst, karst, and karst vegetation restoration landforms in a National Nature Reserve, Caohai (Guizhou Province, China), were compared. The content distribution characteristics of SOC, ROC and DOC were investigated, as well as the geomorphology, spatial locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…SOM is central to soil fertility and vegetation recovery [28,29] . Related studies have shown that N limits early-mid-stage karst ecosystem recovery [30] .…”
Section: Planting a Munitus To Improve Krd Soil Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOM is central to soil fertility and vegetation recovery [28,29] . Related studies have shown that N limits early-mid-stage karst ecosystem recovery [30] .…”
Section: Planting a Munitus To Improve Krd Soil Conditionsmentioning
confidence: 99%
“…The SOM, TN, and AN were signi cantly elevated in SA compared to SC. SOM is pivotal for soil fertility [28] and vegetation recovery [29] . Related studies have revealed that nitrogen constraints early-mid-stage karst ecosystem recovery [30] .…”
Section: Planting a Munitus To Improve Krd Soil Conditionsmentioning
confidence: 99%